Keanekaragaman dan Patogenisitas Fusarium spp. Asal Beberapa Kultivar Pisang - Widya Sari; Suryo Wiyono; Ali Nurmansyah; Abdul Munif; Roedhy Poerwanto (Jurnal Fitopatologi Indonesia, 2017)
Fusarium wilt disease caused by pathogenic fungus F. oxysporum f. sp. cubense is an important disease in banana plants. This research was aimed to identifiy Fusarium spp. collected from banana plants showing wilt disease based on morphology and molecular characters.  The fungi isolates obtained was further examined for its pathogenicity and distribution in various parts of banana plants.  Based on morphological characters, i.e. growth rate, total conidia, colony color, macroconidium, microconidium, and chlamydospores, F. oxysporum f. sp. cubense can be differentiated from other species of Fusarium, but not the strain. Molecular analysis using specific primers VCG 01213/16 and Foc1/Foc 2 successfully identified 13 and 7 isolates of F. oxysporum f. sp. cubense TR4 and F. oxysporum f. sp. cubense non TR4, respectively.  Analysis using universal primer ITS4/ITS5 identified 7 isolates of F. solani, 1 isolate of F. verticillioides, and 2 isolates non Fusarium.  Infection of F. oxysporum f. sp. cubense TR4 and non-TR4 were found mostly in pseudo stems, whereas F. solani and F. verticillioides dominantly colonized banana corm. Pathogenicity test showed that F. oxysporum f. sp. cubense TR4 and non-TR4 caused necrosis on corm of cv. Ambon Kuning.  Similar necrosis symptom was also observed on infection of F. solani but with less severity.